Interactive 3D house marketing / Abu Bakar Mohamed - Mohamed, Abu Bakar (2004)
The recognition of interactive 3D web page on the Internet is now gaining significant momentum. Nowadays, there are profusions of reputable web pages on the Internet which are advertising a variety of fields but web pages with 3D element is a quite new thing. Interactive 3D House Marketing is developed in order to give new perspective and altering the style of presentation of conventional web pages that are also advertising about houses. Through this interactive 3D web page, user can view 3D houses alike the houses in the real world. On the other hand, user is also able to order the houses through this web page. Besides that there are some more additional information such as the mortgage calculator, and gave user opportunities to create their own idea of houses. What makes this project different from any other houses marketing web pages is the representation of the houses. Not like any other web pages, Interactive 3D House Marketing represented the 3D environment function, Besides using 3D Studio Max 6 in developing this project, Macromedia Director MX is usinmg for the 3D scripting, Apache has been used as web server; MySQL acts as the database and PHP Scripting to retrieve data from database.